On the Steppe Eagle Nesting of Dagestan - Nikolai V. Tsapko; Gadzhibek S. Dzhamirzoev; Artem A. Kesyan; Arslan Kh. Khalidov; Umar M. Ashibokov; Vladimir M. Dubyansky (Пернатые хищники и их охрана)
Steppe Eagle (Aquila nipalensis) is a nesting, migratory, and partially wintering species in Dagestan. It is listed in the Red Books of the Russian Federation and the Republic of Dagestan. Until the middle of the last century, Steppe Eagle was found nesting from the lower reaches of the Kuma River to the northern arid foothills, and by the end of the century it practically disappeared from the region, occasionally being recorded during breeding period in the extreme northwest of the republic, the Agrakhan Peninsula and the foothills of the Buynak Basin (Behme, 1925; Volchanechky, 1959: Kharchenko, 1968; Dzhamirzoev, Bukreev, 2020; our data).